2019
DOI: 10.3390/s19204458
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Electrode Locations for Wearable Single-Lead ECG Monitoring Devices: A Case Study Using WFEES Modules Based on the LANS Method

Abstract: Body surface potential mapping (BSPM) is a valuable tool for research regarding electrocardiograms (ECG). However, the BSPM system is limited by its large number of electrodes and wires, long installation time, and high computational complexity. In this paper, we designed a wearable four-electrode electrocardiogram-sensor (WFEES) module that measures six-channel ECGs simultaneously for ECG investigation. To reduce the testing lead number and the measurement complexity, we further proposed a method, the layered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…In this study, the MC-100 was patched 45° from the inter-nipple line to record lead II signals at the precordium. This position conformed to the optimal position for wearable single-lead ECG devices [ 23 ]. Detailed specifications of MC-100 are described in Table 1 .…”
Section: Methodsmentioning
confidence: 65%
“…In this study, the MC-100 was patched 45° from the inter-nipple line to record lead II signals at the precordium. This position conformed to the optimal position for wearable single-lead ECG devices [ 23 ]. Detailed specifications of MC-100 are described in Table 1 .…”
Section: Methodsmentioning
confidence: 65%
“…Since certain arrhythmias attack occasionally and transiently, these patients were requested to wear the CarePatch™ ECG patch continuously for as long as possible within 7 days (the patch is cleared for 7-day continuous ECG monitoring). The device collected the wearable non-standard lead ECG signals at the recommended electrode location [ 32 ] as shown in Figure 2 . The sample rate of the ECG signals is 256 Hz, and the resolution is 12-bit.…”
Section: Methodsmentioning
confidence: 99%
“…One study reported that the best orientation was diagonally on the chest and the best locations were around the chest electrodes of standard precordial leads V 2 to V 4 for the QRS complex and above the leads V 1 and V 2 for the P wave [34]. Another study reported that the best orientation was diagonally sloping downward to the left and the best location was above leads V 1 -V 4 [35]. However, their diagonal orientation also included an extension of the inter-electrode distance.…”
Section: Optimization Of Recording Condition Of a Single-lead Electrocardiogrammentioning
confidence: 99%